2021
DOI: 10.3390/ani11030598
|View full text |Cite
|
Sign up to set email alerts
|

Step by Step about Germ Cells Development in Canine

Abstract: Primordial germ cells (PGCs) have been described as precursors of gametes and provide a connection within generations, passing on the genome to the next generation. Failures in the formation of gametes/germ cells can compromise the maintenance and conservation of species. Most of the studies with PGCs have been carried out in mice, but this species is not always the best study model when transposing this knowledge to humans. Domestic animals, such as canines (canine), have become a valuable translational resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 135 publications
(186 reference statements)
0
7
0
Order By: Relevance
“…We found that the gene expression levels of OCT4, NANOG, c-KIT, DAZL, STRA8, BOULE, and PIWIL2 increased remarkably in the bovine testis from the fetal to adult stage. It has been reported that the OCT4 and NANOG expression expands from gonocytes in the neonatal testis to spermatocytes and round spermatids after sexual maturation, which may explain the increased expression levels found in the adult stage ( 25 , 26 ). In concordance with these results, we immunodetected NANOG across the spermatogenic epithelium of the fetal testis with a high intensity in the Sertoli and pre-spermatogonial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the gene expression levels of OCT4, NANOG, c-KIT, DAZL, STRA8, BOULE, and PIWIL2 increased remarkably in the bovine testis from the fetal to adult stage. It has been reported that the OCT4 and NANOG expression expands from gonocytes in the neonatal testis to spermatocytes and round spermatids after sexual maturation, which may explain the increased expression levels found in the adult stage ( 25 , 26 ). In concordance with these results, we immunodetected NANOG across the spermatogenic epithelium of the fetal testis with a high intensity in the Sertoli and pre-spermatogonial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with these results, we immunodetected NANOG across the spermatogenic epithelium of the fetal testis with a high intensity in the Sertoli and pre-spermatogonial cells. Even though the roles of FRAGILIS and c-KIT have not been deeply studied in cattle, the expression of both genes occurs early in development, where they activate important mediators of postnatal meiotic and post-meiotic GC ( 26 ). In addition to the increasing expression levels of DAZL in the bovine testis during development, our analyses immunodetected DAZL mainly in the peripheral areas of bovine fetal seminiferous tubules associated to Sertoli and pre-spermatogonial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first step is establishment of the chromosomal sex and begins the differentiation process. Sexual differentiation continues in sequential order to gonadal and phenotypical differentiation throughout gestation as the fetus responds to the hormonal or molecular signaling for normal development ( 1 , 2 ). In canines, the initiation of gonadal sexual differentiation begins around day 35–40 in gestation for distinguishing cell lines for male or female morphology ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual differentiation continues in sequential order to gonadal and phenotypical differentiation throughout gestation as the fetus responds to the hormonal or molecular signaling for normal development ( 1 , 2 ). In canines, the initiation of gonadal sexual differentiation begins around day 35–40 in gestation for distinguishing cell lines for male or female morphology ( 1 ). The gonadal ridge develops around day 30–35 in gestation and this undifferentiated ridge will migrate and transform according to specific inputs for female vs. male morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation